In vitro Probiotic Potential and Anti-cancer Activity of Newly Isolated Folate-Producing Streptococcus thermophilus Strains - Tarrah, Armin; Castilhos, Juliana de; Rossi, Rochele Cassanta; Duarte, Vinicius da Silva; Ziegler, Denize Righetto; Corich, Viviana; Giacomini, Alessio (Frontiers in Microbiology, 2018)
Most probiotic strains commercially available today are lactic acid bacteria. Within this functional group, Streptococcus thermophilus is a thermophilic species widely used as starter culture for a huge number of dairy products. Besides being rapid acidifiers, many S. thermophilus strains are able to produce and release folate during growth but, unfortunately, they are seriously impaired during passage through the human gastrointestinal tract. In this work we studied eight S. thermophilus strains isolated from dairy environments in Italy, which already had shown technologically interesting properties, to evaluate their possible probiotic potential and cytotoxicity against cancer cells in vitro. All strains were also evaluated for some health-related properties such as susceptibility to most common antibiotics, hemolytic activity, resistance to simulated gastrointestinal conditions, bile salts hydrolytic activity, production of folate, adhesion to HT-29 human colorectal adenocarcinoma cells and cytotoxic activity against cancer cells. Results revealed that two fast acidifying S. thermophilus strains were found to possess in vitro probiotic properties along with anticancer activity and production of folate. These properties resulted similar and, in some cases, superior to a reference commercial probiotic strain, L. rhamnosus GG. These finding encourage further in vivo studies to evaluate the actual health benefits of these strains on the human host.